Optimizing The Utilization of Electronic Promotion System Services (SISPEK) in Gorontalo Province - Toena, Yulyanda; Rachman, Ellys; Thalib, Tety (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This study is conducted in optimizing the implementation of an electronic job promotion system within the Regional Civil Service Agency of Gorontalo Province. The objective of this study was to assess the implementation of SISPEK in proposals for the promotion of civil servants. This research employed a qualitative approach, wherein data were collected through interviews and observations. Results indicated that limited socialization and administrators' inadequate IT skills crippled exploitation of the system. Meanwhile, infrastructure enhancement stood as a vital role to further accelerate the efficiency in proposals. More socialization and training should be organized to support and ensure the optimum utilization of SISPEK.